Idea of war in the theory of Arnold J. Toynbee - Bukowska, Sonia (Folia Philosophica, 2004)
The article focuses on the problem of a historiosophical aspect of war considered against the background of the theory of an English philosopher, A.J. Toynbee. A reflection on the influence of wars on history constitutes one of the most important issues in this theory. A separate work entitled War and Civilization, which constitutes of many fragments of a multivolume work entitled, A Study of History, is devoted to the above problem. Toynbee considers war from the point of view of histories of individual civilizations because he represents the so-called civilization trend in historiosophy, which considers civilization the smallest unit of a historical research. He expresses a view that war has to be seen as a means of selfannihilation of such institutions as slavery, caste, and class struggle, which have an unfavorable influence on civilized populations. In order to illustrate the destructive influence of war on the history of civilization he refers to the idea of militarism, which he understands as a desire of being at war for its own cause without a justifiable target or necessity. Referring to historical facts, he attempts at proving that the consequences of such activity have always been tragic at the end of the day - the civilization saturated with militarism no longer exists. He claims that the future of humanity depends on the ability of a proper advantage of this knowledge.